2020
DOI: 10.1101/2020.04.07.030304
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

In vetro study on the toxic effects of acrylamide on blood antioxidants, ameliorative effects of vitamin C

Abstract: Background: Acrylamide (ACR) is a naturally occurring, widely used compound, it is generated during cocking carbohydrate rich food at high temperature. Ingestion of large amounts of ACR underlies several health concerns and teratogenicity. Ascorbic acid (vit C) is a strong reducing agent greatly used to clean free radicals. Materials and methods:Blood sample was obtained from 46 years old, healthy nonsmoking man in heparinized tubs. Blood sample was immediately divided into seven parts as triplet for each. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 29 publications
(24 reference statements)
0
2
0
Order By: Relevance
“…Upregulation of GPx, an important antioxidant enzyme, may indicate attenuated antioxidative response in subjects with the highest consumption of acrylamide [52]. Ghamdi et al [53] also showed a significant decrease in the concentration of GPx in healthy men after acrylamide ingestion, but authors also revealed GR depletion, which was not observed in the authors' study group [53]. However, the authors also noticed an students, but the authors did not observe any significant differences in subgroups divided by BMI value.…”
Section: The Nitrates and Acrylamide And Redox Status O R I G I N A L...mentioning
confidence: 74%
See 1 more Smart Citation
“…Upregulation of GPx, an important antioxidant enzyme, may indicate attenuated antioxidative response in subjects with the highest consumption of acrylamide [52]. Ghamdi et al [53] also showed a significant decrease in the concentration of GPx in healthy men after acrylamide ingestion, but authors also revealed GR depletion, which was not observed in the authors' study group [53]. However, the authors also noticed an students, but the authors did not observe any significant differences in subgroups divided by BMI value.…”
Section: The Nitrates and Acrylamide And Redox Status O R I G I N A L...mentioning
confidence: 74%
“…According to Zhao et al [53] GSH depletion is indicated as the final consequence of increased acrylamide exposure, since glycidamide can be conjugated to GSH as a detoxifying pathway of acrylamide. In general, most available literature data indicate OS induction by acrylamide, which is characterized by intensive lipid peroxidation (reflected by 8-iso-prostaglandin-F2α elevation), oxidative DNA damage (8-hydroxy-deoxyguanosine elevation), increased levels of protein-carbonyl as well as a decreased intensity of enzymatic and non-enzymatic antioxidant processes [56].…”
Section: Limitations Of the Studymentioning
confidence: 99%